2011
DOI: 10.4236/jep.2011.21008
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Chromate Removal by Chromium-Resistant Bacillus sp. Isolated from Tannery Effluent

Abstract: A chromate-removing strain was isolated from spent chrome effluent and identified as Bacillus circulans strain MN1. The isolated strain was studied for resistance to Cr (VI) and its ability to remove Cr (VI). The strain was found to tolerate Cr (VI) concentration as high as 4500 mg/L, but the cells growth was heavily influenced when initial Cr (VI) concentration was increased between 1110 mg/L and 4500 mg/L while Cr(VI) at 500 mg/L to 1110 mg/L did not suppressed the cells growth. The experiments also demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Moreover, it has been reported that some Bacillus species are able to tolerate up to 100mg/ml of Cr within their culture media [39]. In another study, Bacillus circulans MN1 tolerated a Cr concentration of 1110 mg/L [40]. These are in concordance with the results obtained in this study.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, it has been reported that some Bacillus species are able to tolerate up to 100mg/ml of Cr within their culture media [39]. In another study, Bacillus circulans MN1 tolerated a Cr concentration of 1110 mg/L [40]. These are in concordance with the results obtained in this study.…”
Section: Resultssupporting
confidence: 82%
“…The isolate was grown in MRS broth (HiMedia, M369), without heavy metals at 37°C for 24 h. After incubation, the optical density of the broth culture was adjusted to OD600 = 0.1 using a light spectrophotometer (JENWAY, 7305). A loopful of the broth culture was then aseptically streaked onto MRS agar (HiMedia, M641) supplemented with different heavy metals (Hg, Cr, Cd, and Pb), respectively, at different concentration (10,20,30,40, and 50 ppm). The plates were then incubated at 37°C for 48 h. Single colonies or trace of growth was ignored.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…Chromium compounds can lead to mutation and cancer, and inhibit enzymes and nucleic acid synthesis. In contrast, chromium (III) is less toxic and less mobile [2]. Chemical methods are available for removal of chromium in bulk from industrial effluent but they often fail to meet the environmental regulations.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction/detoxification of Cr (VI) by microbes is, however, inexpensive and environmentally safe approach and provides a viable option to protect the environment from chromium toxicity. The reduction of Cr (VI) has been reported in Bacillus (Elangovan et al, 2006;Chaturvedi, 2011), Pseudomonas sp. (Rahman et al, 2007), Escherichia coli (Bae et al, 2005), Microbacterium (Pattanapipitpaisal et al, 2001), Ochrobactrum intermedium (Faisal and Hansnain, 2005) and Micrococcus (Sultan and Hasnain, 2005).…”
Section: Introductionmentioning
confidence: 99%